Biological performance of Leptoglossus zonatus (Dallas) (Hemiptera: Coreidae) on corn genotypes - Canassa, Vinícius Fernandes [UNESP]; Medeiros, Fabiana Campos [UNESP]; Bastos, Luiz Felipe Souza [UNESP]; Faria, Rodrigo Donizeti [UNESP]; dos Santos, Thais Lohaine Braga [UNESP]; Cabral, Isabella Rubio [UNESP]; Lourenção, André Luiz; Baldin, Edson Luiz Lopes [UNESP] (FapUNIFESP (SciELO), 2023)
Corn, Zea mays (L.), is one of the most expressive crops in Brazil, due to its wide-ranging uses as animal feeding, biofuel production or used for human consumption. However, there is a huge gap between the actual yield and the natural yield potential of the crop, due to insects’ attack. Leptoglossus zonatus (Dallas) (Hemiptera: Coreidae) is a key corn pest in seed producing regions, due to its attack on corn ears. Plant resistance is a valuable tool for Integrated Pest Management systems and may maintain insect populations at a level that is below an economic or damage threshold. This study aimed to evaluate the biological performance of L. zonatus in different corn genotypes, under laboratory conditions, searching for possible characterization of antibiosis/antixenosis. To achieve this goal, ten nymphs (1st instar) were transferred to polyvinylchloride (PVC) ring containing a corn ear (R6) of each genotype. Each ring corresponded to one replicate, for a total of five replicates per genotype in a completely randomized design. The parameters assessed included the duration of each instar, nymphal period, nymphal survival (%), percentage of mortality of each nymphal stage, adult longevity, and adult weight. The results demonstrate that XB 8018 Bt, 30F53, IAC Airan, XB 8030 and 30F53 YHR genotypes reduced the mean survival and caused high mortality of L. zonatus nymphs at the second instar (above 75.00%) indicating the occurrence of antibiosis/antixenosis. The higher mortality rates were observed at the second nymphal instar.
Keywords: antibiosis; antixenosis; leaf-footed bug; Zea mays